The Spiritual Life of Teleilat Ghassul and Building 78 - Greet, Ben (Near Eastern archaeology, 2021)
Teleilat Ghassul is a 20 ha Chalcolithic site, likely dating to between 4500-4250 BCE (Gilead 2011: 14), that consists of many interconnected domestic buildings interspersed with rooms containing elaborate frescoes. The discovery of infant burials, ritual objects, and frescoes points toward an elaborate spiritual life of the community that inhabited the site. The aim of this paper is to explore an aspect of that spiritual life in detail through a reexamination of the frescoes of Building 78 on Tell 3. Building 78 provides an excellent opportunity for this type of study, as its context links it with Drabsch’s (2015a: 52) model of lineage houses and their centrality to the spiritual life of Ghassul. Through a reinterpretation of the bird fresco and spook masks focused on their connection to the ecology of the region, I hope to demonstrate that these frescoes were thematically linked through concepts of spiritual liminality and annual cycles. This thematic link can then be used to posit the types of rituals that may have been performed by the Ghassulian community within Building 78.